2005
DOI: 10.1152/physiolgenomics.00251.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the left ventricles in a rat model of intrinsic aerobic running capacity

Abstract: Our previous work found DA rats superior for intrinsic aerobic running capacity (ARC) and several cardiac function indexes compared with Copenhagen (COP) rats, and identified ARC quantitative trait loci (QTLs) on rat chromosomes 16 (RNO16) and 3 (RNO3). The purpose of this study was to use these inbred rat strains as a genetic substrate for differential cardiac gene expression to identify candidate genes for the observed ARC QTLs. RNA expression was examined globally in left ventricles of 15-wk-old DA, F1(COP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…2), consistent with our previous results (1,19,23,39). COP.DA(chr 16) rats had a significantly greater mean best distance run to exhaustion of 696.7 Ϯ 38.2 m compared with COP rats (P ϭ 0.03; Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2), consistent with our previous results (1,19,23,39). COP.DA(chr 16) rats had a significantly greater mean best distance run to exhaustion of 696.7 Ϯ 38.2 m compared with COP rats (P ϭ 0.03; Fig.…”
Section: Resultssupporting
confidence: 91%
“…Our laboratory has consistently found greater heart and left ventricular weights for the high-performing DA strain compared with the low-performing COP strain (1,19,23,39). Expression profiling of the left ventricles of these strains also identified two networks of coordinately regulated, differentially expressed genes whose annotations suggested involvement in cell growth, metabolism, death, and differentiation (23).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A number of studies have indicated that gender differences play a role in the overall response to sepsis and hemorrhage, as well as in the functional recovery of endotoxin associated left heart dysfunction [82][83][84][85][86]. In these instances, females tend to have a higher degree of cardioprotection and lower levels of proinflammatory cytokines compared to their male counterparts [6,78,87].…”
Section: Endotoxemiamentioning
confidence: 99%